2022
DOI: 10.1177/21582440221086659
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reading Strategy Instruction on Reading Comprehension, Strategy Use, Motivation, and Self-Efficacy in Chinese University EFL Students

Abstract: This study investigated the effect of explicit reading strategy instruction on reading comprehension, reading strategy use, reading motivation, and reading self-efficacy in Chinese university EFL learners. A total of 117 first-year university students were randomly assigned to either the experimental group or the control group. Students in the experimental group received a 16-week reading strategy training embedded into their English reading classes. The data were collected through five major instruments: a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 38 publications
3
30
1
Order By: Relevance
“…In line with this, many other past studies have corroborated that the teaching of metacognitive strategies indeed helps to motivate ESL and EFL learners to be feel more motivated as they are aware of the trick of utilising the strategies learned to tackle the reading task given to them (Chin, 2019;Li et al, 2022;Tamin & Buyukahuska, 2020). To put into simpler words, when learners are conscious of the variety of metacognitive strategies which can be employed in various reading tasks, they further motivate them to make use of these strategies to become better readers.…”
Section: Motivation In Readingsupporting
confidence: 52%
See 4 more Smart Citations
“…In line with this, many other past studies have corroborated that the teaching of metacognitive strategies indeed helps to motivate ESL and EFL learners to be feel more motivated as they are aware of the trick of utilising the strategies learned to tackle the reading task given to them (Chin, 2019;Li et al, 2022;Tamin & Buyukahuska, 2020). To put into simpler words, when learners are conscious of the variety of metacognitive strategies which can be employed in various reading tasks, they further motivate them to make use of these strategies to become better readers.…”
Section: Motivation In Readingsupporting
confidence: 52%
“…12. Li et al (2022) The independent sample t-test results showed that there was a significant difference between the experimental group and the control after the participants from the experimental group received metacognitive reading strategy instruction.…”
Section: Kung and Aziz (2020)mentioning
confidence: 95%
See 3 more Smart Citations